2017
DOI: 10.22161/ijeab/2.4.42
|View full text |Cite
|
Sign up to set email alerts
|

Proximate analysis and in-vitro gas production of predominant forages in Afe Babalola University rangeland as feed resources for ruminant production

Abstract: Abstract-In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Obua et al (2012) also reported higher crude fibre of (21.69%) and ash (9.79%) probably due to soil type, stage of growth and season of the year. The values obtained for crude protein, ether extract, crude fibre, moisture content, ash and metabolizable energy fell within the ranges obtained by previous studies (Aduku, 1993;Ikhimioya and Olagunju 1996;Tewe, 1997;Bamigboye and Oluwarinde, 2017). The feed intake of the finisher broiler chickens improved significantly (P < 0.05) as the level of Calopogonium mucunoides leaf meal supplemented with yeast increased in their diets (Table 3).…”
Section: Discussionsupporting
confidence: 85%
“…Obua et al (2012) also reported higher crude fibre of (21.69%) and ash (9.79%) probably due to soil type, stage of growth and season of the year. The values obtained for crude protein, ether extract, crude fibre, moisture content, ash and metabolizable energy fell within the ranges obtained by previous studies (Aduku, 1993;Ikhimioya and Olagunju 1996;Tewe, 1997;Bamigboye and Oluwarinde, 2017). The feed intake of the finisher broiler chickens improved significantly (P < 0.05) as the level of Calopogonium mucunoides leaf meal supplemented with yeast increased in their diets (Table 3).…”
Section: Discussionsupporting
confidence: 85%
“…The NRC (National Research Council) suggests that a modest range of 11.0%-14.0% crude protein is recommended for ruminant production. In line with this, Devendra and McLeroy (1982) noted that 11.0% crude protein is considered ideal for achieving normal weight gain in goats, as reported by Bamigboye et al (2013). To overcome the issue of low crude protein in OPF, one strategy is to utilise the upper one-third portion of the OPF, which contains more leaflets.…”
Section: P R E S Smentioning
confidence: 92%
“…These animals are exposed to numerous constraints, characterized by poor housing and poor nutrition, high incidence of diseases, poor breeding methods, among others (Sanusi et al, 2010). The direct competition with man and industries for feed resources as well as the inadequacy of year round feed availability, mainly because of the seasonal fluctuation leading to wide fluctuations in the quantity and quality of forage available to animals has being a major limiting factor in sheep production (Bamigboye et al, 2013).…”
Section: Introductionmentioning
confidence: 99%